The Accomplishment of Individual Actions as a Duty on Moral Responsibility for the Growth of Humanism: A Comparative Study on Buddhist and Yogic Teachings - Perera, Randika ca. 20./21. Jh. (Contemporary buddhism, 2024)
Buddhist and Yogic teachings have illustrated humanistic ethical teachings related to the growth of humanism. Individual actions performed as a duty of moral responsibility is a major theme in the humanistic ethical teachings of Buddhism and Yoga. Considering this significance this study evaluates the Buddhist and Yogic concepts of moral responsibility of the individual and its utility of performing that virtue as a duty in action, and its positive impact on the growth of humanism with reference to the teachings of early Buddhism and Yoga philosophy. Buddhist teachings emphasize that every individual has free will for their moral living and the potential to avoid immoral conduct according to the teachings of the moral measurements. Moreover, Buddha highlights that individuals need to perform their moral responsibility both individually and socially. However, the Yoga philosophical viewpoint on performing moral responsibility as a duty is described in the concept of Nishkama Karma, or performing individual actions selflessly and desire less as a duty. These teachings emphasize that each tradition has highlighted the fundamental ethical teachings of other religions, but the teachings of Buddhism have directed individuals to make moral responsibility a duty with the potential of free will. In comparison to Buddhism, Yogic teachings emphasize performing moral responsibility as a duty in selfless service. Therefore, Buddhist and Yogic teachings have presented more pragmatic teachings for the growth of humanism from a moral perspective and are universally applicable.